1998
DOI: 10.1021/jm980335f
|View full text |Cite
|
Sign up to set email alerts
|

Novel Calcium Antagonists with Both Calcium Overload Inhibition and Antioxidant Activity. 1. 2-(3,5-Di-tert-butyl-4-hydroxyphenyl)-3-(aminopropyl)thiazolidinones

Abstract: A series of 2-(3, 5-di-tert-butyl-4-hydroxyphenyl)-3-(aminopropyl)thiazolidinones was synthesized in order to explore novel calcium antagonists with potent antiischemic activity. These compounds were designed to have, in addition to Ca2+ antagonistic activity, both Ca2+ overload prevention and antioxidant activity in one molecule. These three kinds of activity were evaluated by using a K+-depolarized rat aorta, a veratridine-induced Ca2+ overload model of rat cardiomyocytes, and a soybean lipoxygenase-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Panetta et al reported the anti-inflammatory effect of several 4-thiazolidinones [7]. A number of thiazolidinones have been shown to possess antioxidant and calcium overload inhibiting activities [8]. Suitably substituted thiazolidinones have been reported to reduce serum cholesterol, triglyceride, and glucose levels in our laboratory [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Panetta et al reported the anti-inflammatory effect of several 4-thiazolidinones [7]. A number of thiazolidinones have been shown to possess antioxidant and calcium overload inhibiting activities [8]. Suitably substituted thiazolidinones have been reported to reduce serum cholesterol, triglyceride, and glucose levels in our laboratory [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of N-C-S linkage in the compounds has been shown to have hypnotic, 2 anti-cancer, 3 cardiovascular, 4 antioxidant, 5 anti-inflamatory, 6 antitubercular, 7 antihistaminic, 8 antimicrobial, 9 anticonvulsant, 10 antiviral and anti-HIV 11 acivities. Besides, carbazole, pyrazole and tiazole skeletons constitute the structural core element of many natural and synthesized products.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is no surprise that BHT has been modified to prepare a series of new antioxidants having new medicinal properties in the pharmaceutical industry [ 12 , 22 , 23 ]. Recently, qualitative SARS and rational-design strategies for antioxidants have been used to combine multiple functions; including various multiple antioxidant properties such as radical-scavenging ability and diversified pharmacological activities to offer hybrid compounds, which can exert multiple pharmacological functions through one molecular framework [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%